Local anesthesia and anxiolytic techniques for oculoplastic surgery - Ing EB (Dove Medical Press, 2019)
Edsel B Ing,1 Justine Philteos,2 Galina Sholohov,3 David Ta Kim,1 Navdeep Nijhawan,1 Patrick W Mark,4 Jaclyn Gilbert4 1Department of Ophthalmology and Vision Sciences, University of Toronto, Toronto, ON, Canada; 2School of Medicine, University of Toronto, Toronto, ON, Canada; 3Barzilai Medical Center, Ashkelon, Israel; 4Department of Anesthesia, Michael Garron Hospital, University of Toronto, Toronto, ON Canada Abstract: This study discusses local anesthetic agents, administration techniques, ancillary considerations, and safety precautions for oculoplastic surgery including eyelid, lacrimal, orbital, and temporal artery biopsy procedures. Methods for reducing patient apprehension and discomfort including systemic premedication, topical pre-anesthetic, visual, auditory and tactile distraction techniques, regional blocks, small gauge needles, warmed lidocaine, and buffered lidocaine are discussed. Keywords: local anesthesia, anxiolytics, oculoplastics, eyelid, orbit, lacrimal, temporal artery biopsy